52.4: Properties of High Bonding Force Ultra‐Violet Induced Debonding Adhesives Film and Application on Process of Flexible AMOLED Modules Lamination. (26th August 2021) - Huang, Walter; Lin, Yu-Chen; Feng, Chao
Abstract : Flexible active‐matrix organic light emitting diode (AMOLED) displays are adopted by smart phones which will soon be expanded in applications in the next few years. Displays with curved surfaces on both sides or surround designs have gradually become mainstream and are widely used in the terminal consumer market. For the purpose to respond to the design of curved surfaces on both sides of the mobile phone display mode, when the flexible AMOLED display is assembled, the display areas on both sides need to be temporarily bent and fixed. Due to the limitation of the mobile phone mechanism exterior design, the temporary bonding of the bent areas on both sides is required. Use ultra‐violet (UV) induced debonding adhesives film with higher bonding force for temporary bonding, however the present mainstream UV induced debonding adhesives film from Japan and South Korea mostly only has an adhesive force before UV irradiation below 2, 400 gf/25mm, for the bonding areas on both sides of the shorter and longer sides, Insufficient adhesion and bonding failure often occur, resulting in low yield problems. The R&D team of Anhui Film Tech Materials proposed a new high‐polymer recipe of high‐peeling force UV induced debonding adhesives, which has increased the adhesion by 50% compared with the present products which arefrom Japan and South Korea, and it has increased the adhesion by 100% compared with traditional materials. When the adhesion is improved, the stability of the material specifications over time is also ensured, and superior antistatic ability is maintained at the same time.